2019
DOI: 10.1073/pnas.1813952116
|View full text |Cite
|
Sign up to set email alerts
|

Early lineage specification defines alveolar epithelial ontogeny in the murine lung

Abstract: During the stepwise specification and differentiation of tissue-specific multipotent progenitors, lineage-specific transcriptional networks are activated or repressed to orchestrate cell specification. The gas-exchange niche in the lung contains two major epithelial cell types, alveolar type 1 (AT1) and AT2 cells, and the timing of lineage specification of these cells is critical for the correct formation of this niche and postnatal survival. Integrating cell-specific lineage tracing studies, spatially specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(174 citation statements)
references
References 60 publications
10
147
1
Order By: Relevance
“…4G, Table S3, Table S4). Such trajectory bias of AT1 and AT2 genes in this premature alveolar differentiation was reminiscent of their spatial bias during normal alveolar differentiation (27,28). Finally, transcriptomic changes in the quadruple mutant mirrored those induced by Ctnnb1 deletion (11) ( Fig.…”
Section: Single-cell Rna-seq Profiling Of Post-lung-specification Lefmentioning
confidence: 77%
“…4G, Table S3, Table S4). Such trajectory bias of AT1 and AT2 genes in this premature alveolar differentiation was reminiscent of their spatial bias during normal alveolar differentiation (27,28). Finally, transcriptomic changes in the quadruple mutant mirrored those induced by Ctnnb1 deletion (11) ( Fig.…”
Section: Single-cell Rna-seq Profiling Of Post-lung-specification Lefmentioning
confidence: 77%
“…Although morphologic changes between atRA-treated and Cyp26b1 -/lungs were indistinguishable from one another, cell fate changes in atRA-treated lungs did not fully mirror that in Cyp26b1 -/lungs. One possible explanation for this is that distal epithelial progenitors are specified as early as E13.5 and may not be receptive to changes in fate by the first dose of RA at E15.5 (Frank et al, 2019). Cyp26b1 -/lungs are exposed to higher levels of RA throughout lung development potentially leading to a more severe difference in lineage specification.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Cyp26b1 -/lungs contain a higher proportion of AT2 cells after standardizing for the increased number of DAPI + cells per given area. Because proSP-C is not exclusively expressed in AT2 cells during development (Frank et al, 2019), we repeated the analysis utilizing the AT2-cell specific marker, Lamp3 ("Lysosomal associated membrane protein 3" or DC-Lamp). Quantification of AT2 cells using Lamp3 demonstrated a similar increase in Lamp3 + AT2 cells as compared to proSP-C + AT2 cells in Cyp26b1 -/lungs, with the vast majority of AT2 cells expressing both proteins (Supplemental Fig.…”
Section: Cyp26b1 Is Necessary For Distal Epithelial Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 94 ] However, this latter study suggested that bipotent progenitors are rare and most likely remnant undifferentiated cells that remain at the end of branching morphogenesis. [ 94 ] It was further demonstrated that commitment to alveolar fates occurs much earlier than previously appreciated, taking place concurrently with branching morphogenesis, rather than afterwards. The majority of mature alveolar cells are the progeny of unipotent alveolar progenitor cells fated towards either an ATI or ATII cell early in development, with ATII cells being specified first at the most distal tip of the lung and ATI cells being specified just after ATII cells.…”
Section: The Canalicular Stage Of Respiratory Developmentmentioning
confidence: 99%